Preliminary X‐ray crystallographic studies of an N‐terminal domain of unknown function from a putative glycosyltransferase from Streptococcus parasanguinis. Issue 5 (22nd May 2013) - Zhang, Hua; Zhu, Fan; Ding, Lei; Zhou, Meixian; Wu, Ren; Wu, Hui
<x xml:space="preserve">Abstract</x> Serine‐rich repeat glycoproteins (SRRPs) belong to a growing family of bacterial adhesins; they play important roles in bacterial virulence. Fap1, the first SRRP protein to be identified, is glycosylated; while the first two steps of its glycosylation have been determined, the remaining glycosylation steps are unknown. In a search for proteins that might be relevant to the glycosylation of Fap1, a putative glycosyltransferase (GalT1) from Streptococcus parasanguinis was identified. GalT1 possesses a domain of unknown function at the N‐terminus. This domain is highly conserved in bacteria and is a member of a broad superfamily. However, the structure of this domain has not been determined. Here, the conditions used to produce a recombinant version of this protein domain and to grow protein crystals are reported. The crystals obtained belonged to space group C2, with unit‐cell parameters a = 71.0, b = 45.1, c = 78.6 Å, β = 109.6°, and diffracted to 1.55 Å resolution at a synchrotron X‐ray source. This domain does not share sequence identity with proteins of known structures above a level of 12%.